Analisis Pesan Dakwah Streamer Ustaz Abi Azkakia dalam Channel YouTube M-Key Gaming Game Mobile Legends pada Episode Bane Hijrah - Rizki; Kusnadi; Anang Walian (CV. ITTC INDONESIA, 2024)
A da'wah message is a message containing Islamic da'wah material that is conveyed to the recipient of the da'wah. In the era of globalization, technology is developing rapidly. The method of preaching has also been carried out by utilizing modern technology, namely through online games. Ustaz Abi Azkakia has his own uniqueness which makes him different from Ustaz in general, namely because he preaches while playing Mobile Legends, the most popular game among children today. The research entitled